Estimating the burden of influenza‐associated hospitalizations and deaths in Chile during 2012‐2014. Issue 1 (14th February 2018) - Sotomayor, Viviana; Fasce, Rodrigo A.; Vergara, Natalia; De la Fuente, Felipe; Loayza, Sergio; Palekar, Rakhee
Abstract : Background: Influenza is a vaccine preventable disease that causes important morbidity and mortality worldwide. Estimating the burden of influenza disease is difficult. However, there are some methods based in surveillance data and laboratory testing that can be used for this purpose. Objectives: Estimating the burden of serious illness from influenza by means of hospitalization and death records during the period between 2012 and 2014, and using information from Severe Acute Respiratory Illness (SARI) surveillance. Methods: To estimate the Chilean rate of influenza‐associated hospitalizations and deaths, we applied the influenza positivity of respiratory samples tested in six SARI surveillance sentinel hospitals to the hospitalizations and deaths from the records with ICD‐10 codes from influenza and pneumonia. Results: Annually, 5320 people are hospitalized for influenza and 447 die for this cause. The annual influenza‐associated hospitalization rate for the period was 71.5/100 000 person‐year for <5 years old, 11.8/100 000 person‐year for people between 5 and 64 years old; and 156.0/100 000 person‐year for ≥65 years. The annual mortality rate for the period was 0.08/100 000 person‐year for <5 years; 0.3/100 000 person‐year for people between 5 and 64 years; and 22.8/100 000 person‐year for ≥65 years. Conclusions: This is the first study of influenza burden in Chile. Every year an important quantity of hospitalizations and deaths result from influenza infection. In countries in temperate zones, it is important to know the burden of influenza in order to prepare the health care network and to assess preventive intervention currently in practice and the new ones to implementing.